The Influence Of Transformational Leadership And The Organizational Climate Towards Innovative Work Behavior In The Era Of The Industrial Revolution 4.0: Case Study at PT Daiki Aluminium Industry Indonesia, Karawang Regency - Rinsan Hutabarat; Roosganda Elizabeth; Icin Quraysin; Ika Pratiwi; Andi Hasryningsih Asfar; Martinus Tukiran (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The industrial world has entered the industrial revolution 4.0, which is all related to the internet system, and the rotation is very dynamic, requiring every industry to keep up with this new era. To be able to get a competitive advantage, companies can focus on competitive resources. Among the advantages, the company can focus on having transformational leaders and innovative work behavior from all employees. This study examines the effect of transformational leadership and organizational climate on innovative work behavior by taking the smelter industry of PT Daiki Aluminum Industry Indonesia as a case. The sample of this study is 100 permanent employees in the production department. The analysis of this study uses SEM (structural equation model) with Smart PLS version 3.0 as a statistical tool. The result is that transformational leadership has a positive and significant effect on organizational climate. Transformational leadership and organizational climate also have a positive and significant effect on innovative work behavior partially and simultaneously